Gender differentiation of self-regulating mental states of athletes with disabilities: comparative analysis - Prokhorenko, L.; Popovych, I.; Sokolova, H.; Chumaieva, Y.; Kosenko, Y.; Razumovska, T.; Zasenko, V. (Journal of Physical Education and Sport, 2023)
The purpose is to develop a strategy for empirical research on self-regulating mental states of athletes with disabilities; to identify differences in the structure of self-regulating mental states in the male (Group 1) and female (Group 2) samples. Research methods: psychological content parameters of self-regulation were determined using reliable and valid psycho-diagnostic instruments tested in empirical research on sport psychology. Ranking by a module value of the research parameter (Rg) was applied; factor analysis with the method ANOVA with Varimax rotation was used; correlation between the parameters was determined by means of Spearmen` coefficient (rs); significant differences were identified with Student`s t-test. Results. The study substantiates a strategy for empirical research on self-regulating mental states of athletes with disabilities. The ranking of the parameters under study by the level of significance of correlations with self-esteem was performed. Significant differences (?>.05) were found by two content parameters of self-regulation: process (t=-1.2006) and result (t=1.1045). Two graphical factor structures of self-regulating mental states of athletes with disabilities by gender differentiation were created. It was established that the most loaded factors in the male sample (Group 1) are F1 "Value-meaningful" (DG1=22.67%) and F2 "Result-motivated" (DG2=16.23%). It was found that the most loaded factors in the female sample (Group 2) are F1 "Procedural-value" (DG1=23.88%) and F2 "Pragmatically-oriented" (DG2=14.34%). The study substantiates that dominants for athletes with disabilities in Group 1 are meaning-of-life in sporting activities and stable motivation for success. The research emphasizes that a procedural component of sporting activities dominates in female athletes. The smallest number of correlations was registered in Group 1: F4G1 - "Self-worth" and Group 2: F5G2 - "Reflexive", they are the most independent and dangerous ones. Female athletes with the above dominating mental state are too much focused on their "Ego", that reduces concentration on training and competition activities. Female athletes with the self regulating state "Reflexive" spend too much time analyzing their shortcomings, they are too much focused on correction of their mistakes and on an excessively high level of self-criticism that does not contribute to achievement of maximum sport results. Conclusions. The obtained empirical results should be operationalized into tactical preparation for training staff and male and female athletes with disabilities. Differentiation of self regulating mental states can be a considerable tactical advantage in sporting activities of people with disabilities.